1985
DOI: 10.1901/jeab.1985.43-353
|View full text |Cite
|
Sign up to set email alerts
|

Chlordiazepoxide Effects on Ethanol Self‐administration: Dependence on Concurrent Conditions

Abstract: Experiments examined the effects of acute doses of chlordiazepoxide upon ethanol selfadministration in the rat. A concurrent-schedule procedure was used that employed choice between ethanol (5%) and a second fluid (either water or a 1% sucrose solution). When ethanol and water were the available fluids, chlordiazepoxide at doses of 15 and 20 mg/kg reduced ethanol-reinforced responding and intake, with a greater reduction occurring at the 20 mg/kg dose. However, when ethanol and sucrose were concurrently availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
32
3

Year Published

1986
1986
2010
2010

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 37 publications
3
32
3
Order By: Relevance
“…However, stimulus control has a lesser impact on effects of pentobarbital, chlorpromazine, and promazine (Laties, 1972;Katz, 1983). No data is available on whether stimulus control modulates the effects of fluvoxamine or related drugs; therefore additional studies are necessary to interpret the present results in terms of altered stimulus control.Another possible explanation suggested by Samson and Grant (1985) that could relate to our results is that the addition of concurrent food availability alters the demand curve for ethanol (Hursh, 1993). Concurrent access to food could increase the elasticity of demand for ethanol.…”
mentioning
confidence: 57%
See 3 more Smart Citations
“…However, stimulus control has a lesser impact on effects of pentobarbital, chlorpromazine, and promazine (Laties, 1972;Katz, 1983). No data is available on whether stimulus control modulates the effects of fluvoxamine or related drugs; therefore additional studies are necessary to interpret the present results in terms of altered stimulus control.Another possible explanation suggested by Samson and Grant (1985) that could relate to our results is that the addition of concurrent food availability alters the demand curve for ethanol (Hursh, 1993). Concurrent access to food could increase the elasticity of demand for ethanol.…”
mentioning
confidence: 57%
“…Because the rats in this study were not water-deprived, it is unclear that water was reinforcing lever-pressing (as evidenced by low rates of responding on the water-associated lever). The increased resistance to disruption of responding for ethanol by chlordiazepoxide when sucrose was concurrently available did not appear to be due to changes in the baseline rate of responding for ethanol as baseline rates did not differ between conditions (Samson and Grant, 1985).Early studies suggested that selective serotonin reuptake inhibitors (SSRI), including fluvoxamine, could reduce ethanol intake in laboratory animals (Murphy et al, 1985;Maurel et al, 1999). Further research indicated that fluvoxamine could selectively reduce operant responding maintained by ethanol when compared with responding maintained by food (Lamb and Järbe, 2001).…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…The importance of alternative and concurrently available reinforcers in EtOH-maintained responding paradigms has been previously (Carroll et al, 1991;Heyman and Oldfather, 1992;Petry and Heyman, 1995;Rodefer et al, 1999;Samson and Grant, 1985) and recently (June, 2002) addressed. In addition, no studies could be found in the literature that have used neuroanatomical control groups to evaluate site-specific effects on EtOH-motivated behaviors, or motivated behaviors initiated by a palatable alternative solution.…”
Section: Introductionmentioning
confidence: 99%